2002
DOI: 10.1007/s00330-001-1249-2
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral lipoma arborescens associated with early osteoarthritis

Abstract: Lipoma arborescens is a rare disease that has generally been considered to be unilateral. We report a case of bilateral disease in a patient with associated marked premature osteoarthritis of the knees. We postulate a possible association between these two conditions and explain a possible underlying mechanism. We suggest that lipoma arborescens be considered as a rare underlying cause of young patients with bilateral premature osteoarthritis, and recommend MRI as the definitive imaging modality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 10 publications
0
24
0
Order By: Relevance
“…The majority of cases are monoarticular [ 7 ]. In fact, there have been only a few cases of bilateral LA described in the literature [ 2 , 11 , 14 17 ], as were cases five and six of this series. A few reports have described polyarticular involvement [ 6 , 17 ].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The majority of cases are monoarticular [ 7 ]. In fact, there have been only a few cases of bilateral LA described in the literature [ 2 , 11 , 14 17 ], as were cases five and six of this series. A few reports have described polyarticular involvement [ 6 , 17 ].…”
Section: Discussionmentioning
confidence: 77%
“…An association between LA and OA has been postulated [ 14 , 23 ], but the causal relationship between these two entities has not been fully clarified. It has been suggested that the long-standing synovial thickening effusions caused by repeated mechanical injury to the proliferated villi eventually lead to OA [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…The etiology is still unknown, and although it can occur without antecedents, it is associated in the literature with trauma, inflammation, or inflammatory joint diseases, neoplasm, and degenerative conditions (osteoarthritis) [ 14 , 15 ]. There was even one case report describing a relation to infection (septic arthritis) [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The secondary type has been defined as lipomatosis resulting from chronic irritation of the synovium (as seen with degenerative joint disease or arthritis) rather than a true neoplasm and is by far the most common form of lipoma arborescens. Most authors have accepted the last hypothesis [ 14 , 15 , 19 , 20 ]; this suggests that osteoarthritic changes are secondary to the presence of lipoma arborescens. Natera even concludes in his retrospective review that progressive joint degeneration could be prevented or at least delayed, if prompt synovectomy is performed [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation